Uso do complemento alimentar em recém-nascidos a termo submetidos à cesariana eletiva : efeito sobre o aleitamento materno - Machado, Liane Unchalo (2014)
Background and aims: Studies show that offering supplementary formula to the newborn interferes with the maintenance of breastfeeding. However, these studies did not select only term infants born by elective cesarean section. It is important to know the characteristics of this population of newborns to ensure that they are exposed to the same effects of supplement feedings observed in newborns in general. The aim of this study was to evaluate the effect of formula supplement in newborns at term undergoing elective cesarean section. Methods: A cohort study including newborns at term and their mothers, whose deliveries occurred by elective cesarean section at Moinhos de Vento Hospital, a private general hospital located in Porto Alegre city, in South Brazil, was conducted from October 2011 to April 2013. Initial data were obtained from medical records of newborns and through interviews with mothers in the recovery room. Follow-up was done by telephone contact with each mother, at the end of the second week of life, in the third month, and in the sixth month after birth. The proportion of infants who had a food supplement prescribed in the first prescription was evaluated, as well as the use of supplement before and / or after the first 24 hours of life. The chi-square test was performed with the respective residue analysis. To obtain the effects corrected for the influence of other variables, a model of logistic regression was adjusted, having as response variables "exclusive breastfeeding at three months" and "breastfeeding at six months," and as dependent variables those significant at the 30% level in previous analyzes. Quality of fit and significance of the logistic model were verified using the Hosmer and Lemeshow test. Significance of the coefficients of the model was verified by the Wald statistics, and those significant at the 5% level were kept in the model. Data were analyzed with SPSS version 17.0. Results: At all 964 pairs mother / baby were studied, whose median maternal age was 32 years (from 29.5 to 35.5, min., 18 max. 40th). Nineteen (1.9%) mothers started breastfeeding already in the delivery room, and 936 (97.0%) started in the recovery room. In the first prescription, 811 (84.1%) newborns had already formula supplement prescribed, however only 467 (48.5%) actually received it. Of the 964 mothers, 675 (70.0%) were breastfeeding exclusively in the third month. At six months, 781 (81.0%) mothers were still breastfeeding, but 868 (90.0%) had already introduced other foods, and 737 (76.4%) were already working. Infants that were fully breastfeeding at three months comprised: 386/497 (77.7%) infants who never received supplementation; 289/467 (61.8%) who received in-hospital formula at some point (p<0.001); 146/246 (56.9%) who received supplementation before 24 hours of life (P<0.001); and 242/396 who received supplementation after 24 hours of life (P<0.001). After multivariate analysis, it was found that supplement use before 24 hours of life and supplement use after 24 hours of life remained associated with lack of exclusive breastfeeding at three months (p=0.001 and p=0.003 respectively). Conclusions: In this population of babies born by elective caesarean section, even with a good breastfeeding success rate, use of formula supplement in the first hours of life was strongly associated with reduction in exclusive breastfeeding at three months. It should be emphasized the importance of a very careful decision to use supplementation and prescription of formula feedings to newborn infants, as well as the need for justifying the decision in the hospital records.